Seroprevalence of anti-SARS-CoV-2 antibodies and factors associated with infection among adolescent men who have sex with men and transgender women in Salvador, Brazil - Carina C. Santos; Fernanda W. de M. Lima; Laio Magno; Fabiane Soares; Dulce Ferraz; Alexandre Grangeiro; Eliana Miura Zucchi; Marie Préau; Xavier Mabire; Helen R. S. S. Matos; Inês Dourado; the COBra Study Group (BMC, 2023)
Abstract Background Brazil was strongly affected by the COVID-19 pandemic and the impact of the pandemic on sexual and gender minorities' youth remains unknown. This study aimed to estimate the seroprevalence of SARS-CoV-2 antibodies and associated factors among adolescent men who have sex with men (AMSM) and transgender women (ATGW) participants of a human immunodeficiency virus (HIV) pre-exposure prophylaxis cohort study (PrEP1519). Methods This is a cross-sectional design conducted between June and October 2020 in Salvador, Brazil. Serum samples were collected from AMSM and ATGW aged 16-21 years between June-October 2020. IgG and IgM anti-SARS-CoV-2 were detected by chemiluminescence immunoassay, and data were collected through a socio-behavioral questionnaire. Results Among the 137 participants, the seroprevalence of anti-SARS-CoV-2 IgG and IgM was 20.4%; 16.8% of the participants were positive for IgG, and 11.7% for IgM. In the multivariable analysis, the seroprevalence was two times higher among those who never wore masks (OR= 2.22; 95% CI: 1.08-4.57) and among those who believed that they could be easily cured of the disease (OR= 2.05; 95% CI: 1.05-4.01). Conclusions The high seroprevalence of SARS-CoV-2 antibodies among gender and sexual minority youth seems to be informed by behaviors and attitudes that contrast with public health measures and the potential severity of the disease when vaccination was still not available.